A Report on Hydrographic Activities Following the Great East Japan Earthquake - Kato, Shigeru; Sengoku, Arata; Yoritaka, Hiroyuki; Kaneda, Kentaro; Fukae, Kunikazu; Katagiri, Yasutaka; Koso, Yasuhiro; Nakamura, Hitoshi; Toyama, Shinichi; Sato, Mariko; et al. (The International Hydrographic Review, 2012)
The Great East Japan Earthquake (Mw9.0) on 11 March 2011 accompanied with a huge tsunami of more than 10 meters in height devastated many cities and ports along the Pacific coast of northeastern Japan, and claimed nearly 20,000 lives with many of them still missing. This report reviews actions taken by the Japan Hydrographic and Oceanographic Department (JHOD) after this unprecedented disaster. Immediately after the earthquake, the JHOD carried out hydrographic surveys for the urgent need to help clear the passage in ports due to sunken debris swept away by the tsunami. These surveys have enabled the vessels with relief supplies on board for the affected areas to enter the ports. The JHOD revisited the affected ports for the next stage of hydrographic surveys. These surveys will contribute to revised nautical charts based on new data collected after the earthquake, and includes the ongoing restoration and reconstruction work of quays and port facilities. This stage includes the re-determination of the datum level of the affected ports, which is necessary because of large subsidence being reported in the areas. All of these efforts by the JHOD clearly demonstrate the significance of the hydrographic activities in case of the post-quake emergency situation, not only for the safety of navigation but also for economic recovery.